Quantification of metformin and glyburide in blood for paediatric endocrinology - Radamés Alemón-Medina; Juan Luis Chávez-Pacheco; Blanca Ramírez-Mendiola; Liliana Rivera-Espinosa; Raquel García-Álvarez (Instituto Nacional de Pediatría, 2014)
Background: The recent use of antidiabetic drugs such as metformin and glyburide for the treatment and control of childhood obesity, insulin resistance and type II diabetes mellitus in children and adolescents, has encouraged physicians to determine plasma levels of these drugs for the right dose adjustment. Objective: To implement and validate a UPLC-UV method to quantify metformin and glyburide in blood samples. Materials and methods: Only a 0.1 mL-volume blood sample was used. Both drugs are removed by precipitation with methanol. Quantitation was carried out with mobile phase of 4.6 mM potassium phosphate monobasic (KH2PO4) 0.1 M pH = 6.5, sodium dodecyl sulphate (SDS) and acetonitrile (63:7:30), at 0.8 mL/min through a VARIAN Pursuit® C8 150 x 3.9 mm column at 40°C, 236 nm. Results: The method allows the measurement of 20 to 600 nanograms of metformin and from 100 to 2 000 nanograms of glyburide per milliliter of blood. Both drugs are physicochemically stable in blood samples for up to 30 days at 4°C. Conclusion: Our method allows quantification of metformin and gly- buride in paediatric blood samples, to support the clinicians to monitor treatment compliance, bioavailability and pharmacokinetic profiles.